PENGARUH BUDAYA CARE DAN INTEGRITY TERHADAP SIKAP INTRAPRENEURSHIP KARYAWAN PADA KANTOR PUSAT PT PELINDO III (PERSERO) SURABAYA - jurnalpps pps; Didik Trisila (Prodi Magister Manajemen Universitas Wijaya Putra, 2021)
This study aims to determine the influence of a culture of caring and integrity on intrapreneurship attitudes in employees of PT. Pelindo III Surabaya and the sample used was 90 respondents from a population of 258 employees of PT. Pelindo III Surabaya. This research method uses quantitative methods and the analytical technique used is multiple linear regression. The results showed that intrapreneurship can be significantly influenced by a culture of caring and integrity. Caring culture partially influences intrapreneurship. Meanwhile, partial integrity also affects the attitude of intrapreneurship.